Changes in physical-mechanical properties and structure of ferritic-pearlitic steel 15Kh2NMFA caused by severe low-temperature deformation and exposure to alternating magnetic field - Sokolenko, V.I.; Mats, A.V.; Karas’, V.I.; Okovit, V.S.; Chernyak, N.A.; Gorbatenko, V.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
It is shown for the low-plasticity ferritic-pearlitic steel 15Kh2NMFA (2Cr, 1Ni, 0.5Mn, 0.5Mo), subjected to severe rolling deformation at 90 K, that the treatment by the alternating magnetic field results in a substantial decrease of the yield strength and an increase of fracture stress, total elongation, necking and dynamic shear modulus. This is accompanied by reduction of the internal friction background and coercive force. The changes in the physical-mechanical properties and the structure are related to magnetic- and electrical-nature processes giving rise to stress relaxation in the microvolumes with a high density of deformation defects.